2014
DOI: 10.14236/ewic/eva2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Visualisations of Data from the Literacy Tablet Reading Project in Rural Ethiopia

Abstract: Smart phones are ubiquitous; light, portable and indispensable. The spatial, perceptive and visual connections among scene, subject and photographer are different, compared to a regular camera. This fact enables the photographer to focus on different topics, try practices s/he has not tried before. Mobile devices change the way we create, edit, sequence and share photography. When you do street photography with a smart phone camera, one of the advantages is that people do not really understand where you aim at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Since 2015, when the 2030 Agenda for Sustainable Development was adopted at the United Nations General Assembly, many initiatives for the application of digital technologies to policies and programs for development, particularly those associated with SDGs 3 and 4, emerged in various countries, particularly LMICs [ 5 , 29 ]. However, there is insufficient evidence on how digital device use affects children’s cognitive improvement in LMICs [ 8 , 30 , 31 ]. This study focused on urban and rural Cambodian schools to provide a comprehensive perspective on the adoption and use of digital devices among children.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2015, when the 2030 Agenda for Sustainable Development was adopted at the United Nations General Assembly, many initiatives for the application of digital technologies to policies and programs for development, particularly those associated with SDGs 3 and 4, emerged in various countries, particularly LMICs [ 5 , 29 ]. However, there is insufficient evidence on how digital device use affects children’s cognitive improvement in LMICs [ 8 , 30 , 31 ]. This study focused on urban and rural Cambodian schools to provide a comprehensive perspective on the adoption and use of digital devices among children.…”
Section: Discussionmentioning
confidence: 99%
“…The aesthetics of photography has changed as well (Germen, 2014) due to the fact that it has become possible to take images anywhere, at any time and with automatic shutters that in thousands of seconds offer thousands of perspectives on the object or situation photographed. If in part this change had already occurred with the appearance of digital cameras, the fact that the images started to be made with a common object which we carry around at all times further enhanced this possibility.…”
Section: Mobile Phone As a Journalistic Tool: Productionmentioning
confidence: 99%
“…Taking in account children's cognitive development previous researchers identified aspects that should be taken into consideration when designing tablet application for them, such as holding only one thing at memory at time [9] or manifesting centralization, focusing their attention in only one characteristic at time. Other studies identified several children-tablet interactions issues, which can be connected to children's continuously development of motor skills for instance: difficulties with multitouch [16] difficulties with drag and drop interaction [13] not recognized gestures [3] or misinterpreting touch actions [3] [16].…”
Section: Children Cognitive Development Tablet Interaction and Game mentioning
confidence: 99%
“…The tablets were given to children in rural villages in Africa, and the results showed that the children, which took part in the study, encountered technology and literacy for the first time by using the tablet. Their results called attention to the highly collaborative aspect of children's tablet interaction in those communities and that children become passionate learners and also teachers of their community [9].…”
Section: Technology-enhanced Learning For Children Without Access To mentioning
confidence: 99%